Corporate Internet Reporting in emerging economic countries: the Malaysian perspective - Turmin, Siti Zaidah; Abdul Hamid, Fatima; Mohamad Ghazali, Nazli Anum (Universiti Putra Malaysia Press, 2015)
The increasing use of Internet technology in corporate world is undeniable. Corporate Internet Reporting (CIR) is the communication process between the corporate sectors and stakeholders via the medium of the Internet. CIR is a significant way for the corporate sectors in presenting and disseminating business information. The study is conducted with the objective to examine the practice of CIR by the Malaysian listed corporations. Sample of the study consisted of 380 listed corporations. In measuring the level of CIR practice by companies, a CIR index was used. Data for CIR practice were collected by observing the presence of CIR attributes in the websites of companies being investigated and analysed by using descriptive statistics. The findings show that 82 percent of the companies examined have websites and are practicing CIR. On average, Malaysian listed companies practiced around 28.9% of the overall CIR attributes. The results based on industry type showed that the plantation sector had the highest mean score for overall CIR, Investor Relations category and User Support category, whereas the finance sector had the highest mean score for the categories of Accounting and Finance and Technological Advantage, and the construction sector revealed the highest mean score for forward looking data. Furthermore, a comparison between the Main Market and ACE market companies did not show any significant difference in the mean score for the overall CIR attributes and specific CIR attributes. Findings of the study might be useful to the Malaysian listed corporations in better understanding the level of CIR they practised so as to further increase the level of CIR in the near future. Finally, the study adds to the knowledge on the practice of CIR in Malaysia as one of the world's emerging economic countries.